Using triple-layer remote phosphor structures LaVO4:Eu3+ and ZnS:Cu,Sn to improve the chromatic uniformity and luminous quality of WLEDs - Phuc Dang Huu; Dieu An Nguyen Thi; Anh Minh D. Tran (Universitas Ahmad Dahlan, 2022)
This research paper investigates the novel triple remote phosphor layer for improving the remote phosphor’s angular chroma uniformity (ACU) of down-light lamps by using remote micro-patterned phosphor layers (RMPP). In addition, introducing the triple-layer (TL) RMPP is introduced to offer the potential approach to this objective. This analysis also measures the optical efficiency of the layers and the angle distribution of angular correlated color temperature (ACCT). Drawing a comparison between the traditional dual-layer (DL) RMPP and the proposed TL is furthermore critical to this study. According to the findings, the triple-layer phosphor configuration can achieve greater hue consistency while having a correlating colour temperature (CCT) variance merely measured at 441 K. Results in the single RMPP layer are 1390 K of the remote phosphor (RP) sheet setting and 556 K for the ACCT deviation. The recreation employing finite-difference time-domain (FDTD) as well as the approach of ray-tracing ensures an increase in angular color uniformity (ACU). The structure of DL and TL RMPPs results in a 6.68 % and 4.69 % gain in luminous efficiency, respectively, with the standard RMPP layer at a currently driving of 350 mA. The micro-patterned layer’s scattering characteristic and mixing effect may account for the increased ACU and luminous efficiency.